2021
DOI: 10.1177/0192513x20984494
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Constraints of the Partner Market and Educational Assortative Mating

Abstract: This study aims to determine to what extent the opportunities and restrictions of the partner market influence educational assortative mating. It also analyzes the interplay between the opportunity structure and preferences. Matching district-based partner market indicators to heterosexual couples when they move in together based on the German Socio-Economic Panel, we find strong effects of the opportunity structure on educational homogamy. The results further imply that the density of the supply of potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Further research on the interplay of various dimensions of attractiveness on the partner market on the one hand and quantitative meeting opportunities on the other hand could lead to deeper insights into the mechanisms of couples' bargaining processes. Prior research has shown that opportunities and constraints in the partner market are associated with demographic processes such as finding a partner (Eckhard & Stauder, 2019), educational (Stauder & Kossow, 2021) and ethnic homogamy (Kossow, 2020), and marital instability (Stauder & Unsöld, 2021). While these partner market impacts are suspected to be biased by endogeneity, partner market opportunities can be considered completely exogenous to the dyadic division of housework.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research on the interplay of various dimensions of attractiveness on the partner market on the one hand and quantitative meeting opportunities on the other hand could lead to deeper insights into the mechanisms of couples' bargaining processes. Prior research has shown that opportunities and constraints in the partner market are associated with demographic processes such as finding a partner (Eckhard & Stauder, 2019), educational (Stauder & Kossow, 2021) and ethnic homogamy (Kossow, 2020), and marital instability (Stauder & Unsöld, 2021). While these partner market impacts are suspected to be biased by endogeneity, partner market opportunities can be considered completely exogenous to the dyadic division of housework.…”
Section: Discussionmentioning
confidence: 99%
“…In Blau's macrosociological structural theory (Blau, 1977a; 1977b), the population distribution circumscribes the opportunities and limits the choices in a population (Blau, 1977b; Stauder, 2008). Next to finding a partner (Eckhard & Stauder, 2019) and couple homogamy (Stauder & Kossow, 2021), the union stability is affected by the availability of (alternative) partners. For heterosexual individuals, the probability to meet these alternative partners depends on the gender distribution in their social environment (Åberg, 2009, Lyngstad, 2011, McKinnish, 2004, McKinnish, 2007, South, 1995, South & Lloyd, 1995, South et al, 2001, Svarer, 2007, for Germany, see Klein, 1994; Obersneider et al, 2019; Stauder, 2002; Stauder & Unsöld, 2021).…”
Section: The Impact Of the Partner Market On Housework Division: Theo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lower union formation rates and lower union quality may lead to higher childlessness in the population (Rijken and Liefbroer, 2009). Moreover, we hypothesize that a lack of partners could increase childlessness among men with low socioeconomic status in particular, as they have less resources to cope with the heightened competition on the partner market (Stauder and Kossow, 2021).…”
Section: Introductionmentioning
confidence: 94%
“…Research exploring the impact of partner availability on matching quality has indicated that educational mating is influenced by the opportunity structure within the partner market (Grow and Van Bavel, 2015;Stauder and Kossow, 2021;Van Bavel and Nitsche, 2013;Van Bavel et al, 2018). As well as increasing the risk of relationship dissolution, lower matching quality may reduce the likelihood of transitioning to parenthood (Rijken and Liefbroer, 2009).…”
Section: Effects Of Unbalanced Partner Markets On Fertilitymentioning
confidence: 99%